SEROPREVALENCE OF HEPATITIS B SURFACE ANTIGENAEMIA AND ITS RELATIONSHIP TO CD4+ CELL COUNT AMONG HIV-INFECTED PATIENTS IN MAIDUGURI, NORTH EASTERN NIGERIA - GONI BW; YUSUPH H; MUSTAPHA SK; KIDA IM; SAHABI AM; BAKKI B; BABA MM; TALLE AM; GARBATI MA; TAHIR A; ABDUL H (Ntec Specialist, 2011)
Background: Both HIV and HBV infections are endemic in Nigeria and patients with dual HIV/HBV-coinfections are increasingly being recognized because of shared modes of transmission as well as synergy in pathogenesis. Reports have indicated that HBV will contribute significantly to morbidity and mortality among HIV-infected population over the coming years because of increasing access to highly active antiretroviral therapy (HAART). Objective: To determine the prevalence of hepatitis B virus surface antigenaemia among HIV-infected patients and its relationship to CD4+ cell count. Method: A cross-sectional observational study in which 100 newly diagnosed HIV-infected adults comprising 59 (59%) females and 41 (41%) males were selected for the study by systematic random sampling. Results: The age range of the study population was 15-65 years. The mean ages for male and female subjects were 39.37 ± 10.52 and 31.32 ± 7.52 years, respectively. The prevalence of HBsAg among the study subjects was 21%. The mean CD4+ cell count of HBsAg positive subjects was significantly lower than that of HBsAg negative ones i.e. 105.43 cells/µl vs. 161.35cells/µl (p = 0.033). Conclusion: The HIV-HBV confection prevalence of 21% is fairly high and the significantly low mean CD4+ cell count among these subjects suggest that this group of patients are more immunocompromised and may perhaps have increased risk of liver-related morbidity and mortality than their HIV-monoinfected counterparts. Screening for serological markers of chronic HBV infection in all newly diagnosed HIV-positive patients is therefore recommended before commencement of HAART as it also guides the choice of ART regimen, as well as intensification of HBV immunization programmes in all newborns and persons at risk of contracting HBV infection.